An Investigation into the Issues Concerning the Copyright of Content Generated by Text-to-Video AI - Zhou Chunguang; Yi Jia (当代社会科学（英文）, 2024)
Text-to-video artificial intelligence(AI) is a new product that has arisen from the continuous development of digital technology over recent years. The emergence of various text-to-video AI models, including Sora, is driving the proliferation of content generated through concrete imagery. However, the content generated by text-to-video AI raises significant issues such as unclear work identification, ambiguous copyright ownership, and widespread copyright infringement. These issues can hinder the development of text-to-video AI in the creative fields and impede the prosperity of China's social and cultural arts. Therefore, this paper proposes three recommendations within a legal framework:(a) categorizing the content generated by text-to-video AI as audiovisual works;(b) clarifying the copyright ownership model for text-to-video AI works;(c) reasonably delineating the responsibilities of the parties who are involved in the text-to-video AI works. The aim is to mitigate the copyright risks associated with cont